UTILIZING TWITTER DATA TO UDERSTAND GLOBAL HALAL INDUSTRY TRENDS AND DEVELOPMENTS IN THE DIGITAL ERA - Izza, Nadia Nurul; Priantina, Anita; Rusydiana, Aam Slamet (Universitas Airlangga, 2023)
Abstract The research aims to identify and collect issues related to the halal industry discussed by users' activities, sentiments, and content on Twitter. The method used involved collecting 135,050 Twitter conversations over a two-year period from July 21, 2021, to March 15, 2023, utilizing the Drone Emprit Academic (DEA) machine. Text data mining techniques were employed with the assistance of the DEA system, which included sentiment analysis, Social Network Analysis (SNA), and other descriptive analyses. The research findings indicate that the highest number of tweets related to the halal industry originated from Indonesia, followed by Malaysia and the United Kingdom. These tweets were predominantly contributed by millennials and zillennials and were characterized by a 71% positive sentiment, 27% negative sentiment, and 2% neutral sentiment. Furthermore, the Social Network Analysis (SNA) revealed integration and collaboration between the halal industry and Islamic financial institutions, suggesting the potential for creating a halal ecosystem. This research serves as a guideline for policymakers in the halal industry sector to evaluate public sentiment and formulate appropriate advancement strategies. Additionally, this study contributes to a deeper understanding of social media data analysis in the context of the halal industry and offers directions for future research. Keywords: Halal Industry; Text Mining; Sentiment Analysis; Twitter; Drone Emprit Academic.